Sob a égide do capital: renda fundiária e desigualdades na produção do espaço urbano na conurbação da Grande São Luís - Moreira, Tiago Silva (2024)
The present study is structured around the financialization of real estate production and its implications for the urban restructuring of the Ilha do Maranhão. Initially, the thesis addresses the issue of land rent and intra-urban expansion, highlighting how urban space is currently subordinated to capital, transforming the city into a profitable business. The analysis of financialization reveals how capital accumulation processes directly impact the use and occupation of urban land, evidencing a model of urban development that prioritizes the logic of the real estate market at the expense of social needs. The economic formation and productive restructuring in Maranhão are discussed within the historical trajectory of the local economy up to the most recent transformations. Urban space, as a social production, is in a constant process of "implosion-explosion." Productive restructuring is seen as a phenomenon that, while bringing technological innovations and new investments, also perpetuates social and spatial inequalities. The study explores the production and social reproduction of urban space, investigating the influence of the dominant class and the resistance of the working classes. The analysis reveals how the material, symbolic, and social production of urban space reflects the current dynamics of power and economic relations. Public policies and urban interventions are criticized for often favoring private interests, resulting in gentrification and social exclusion. The transition from the modernist/functional planning model to the neoliberal one reinforces the pattern of capitalist development, which demands continuous adjustments in geographic expansion and spatial reorganization. This process is driven by the logic of profitability, financialization, and the private management of collective goods and services, often facilitated by large public investments. The study examines changes in urban legislation and the slow process of land regularization in island municipalities, contextualizing these processes within the real estate financialization scenario. Moreover, the research has a qualitative character, seeking to measure the dynamics between concrete reality and individuals. The main objectives of the thesis include critically analyzing urban planning policies and their consequences for the socio-spatial structure of the cities that make up the conurbation of the Grande São Luís. The research aims to identify the limits of government actions in mitigating urban informality and promoting land regularization, seeking to understand the gaps and limitations of these policies. Among the main conclusions, it is highlighted that the financialization of urban land intensifies socio-economic inequalities, benefiting a privileged minority with access to credit, while excluding the impoverished majority, resulting in significant urban asymmetries. Thus, real estate appreciation and land speculation are identified as key elements in perpetuating social exclusion and the fragmentation of urban space. It is concluded that it is essential to rethink urban planning strategies, incorporating an approach that prioritizes the realities of cities in order to achieve true social justice.